Honduras food system profile: Better understanding food systems at country level - Wiegel, Jennifer Rebecca; Wissen, Denise van; Lundy, Mark M.; Bene, Christophe; Chege, Christine Gacheri Kiria; Hernandez, Ricardo; Achicanoy Estrella, Harold Armando (2023)
Country profiles are more than a simple compilation of national indicators. They are constructed and designed around a common framework and methodology to identify hotspots of unsustainability in the food systems and prioritize interventions at multiple scales to address these through targeted actions and investments. An important feature of the country profiles is that they are co-produced with key public and private food system stakeholders engaged in both identifying the data and validating results and emerging key messages. The use of a common framework also offers an opportunity for a global comparative analysis on food system transitions and transformations – not just at national but also international level – thus generating insights and lessons for decision-makers. We expect these profiles to contribute to relevant international processes, following the UN Food Systems Summit in 2021. This Honduras food system profile (also available in Spanish) is composed of three main blocks of information: (a) system drivers; (b) system components; and (c) system outcomes.